Air quality and radiative impacts of Arctic shipping emissions in the summertime in northern Norway: from the local to the regional scale - Marelle, L.; Thomas, Jennie; Raut, Jean-Christophe; Law, K. S.; Jalkanen, Jukka-Pekka; Johansson, Lasse; Roiger, Anke; Schlager, Hans; Kim, Jin; Reiter, Anja; Weinzierl, Bernadett (Atmospheric Chemistry and Physics, 2016)
In this study, we quantify the impacts of shipping pollution on air quality and shortwave radiative effect in northern Norway, using WRF-Chem (Weather Research and Forecasting with chemistry) simulations combined with high-resolution, real-time STEAM2 (Ship Traffic Emissions Assessment Model version 2) shipping emissions. STEAM2 emissions are evaluated using airborne measurements from the ACCESS (Arctic Climate Change, Economy and Society) aircraft campaign, which was conducted in the summer 2012, in two ways. First, emissions of nitrogen oxides (NOx) and sulfur dioxide (SO2) are derived for specific ships by combining in situ measurements in ship plumes and FLEXPART-WRF plume dispersion modeling, and these values are compared to STEAM2 emissions for the same ships. Second, regional WRF-Chem runs with and without STEAM2 ship emissions are performed at two different resolutions, 3 km × 3 km and 15 km × 15 km, and evaluated against measurements along flight tracks and average campaign profiles in the marine boundary layer and lower troposphere. These comparisons show that differences between STEAM2 emissions and calculated emissions can be quite large (−57 to +148 %) for individual ships, but that WRF-Chem simulations using STEAM2 emissions reproduce well the average NOx, SO2 and O3 measured during ACCESS flights. The same WRF-Chem simulations show that the magnitude of NOx and ozone (O3) production from ship emissions at the surface is not very sensitive (< 5 %) to the horizontal grid resolution (15 or 3 km), while surface PM10 particulate matter enhancements due to ships are moderately sensitive (15 %) to resolution. The 15 km resolution WRF-Chem simulations are used to estimate the regional impacts of shipping pollution in northern Norway. Our results indicate that ship emissions are an important source of pollution along the Norwegian coast, enhancing 15-day-averaged surface concentrations of NOx ( ∼ +80 %), SO2 ( ∼ +80 %), O3 ( ∼ +5 %), black carbon ( ∼ +40 %), and PM2.5 ( ∼ +10 %). The residence time of ...